Optimization of Growth and Development of Toddlers through Increasing Knowledge during Pregnancy, Breastfeeding, Babies & Toddlers - Fitriyani, F; Aisyah, Risqi Dewi; Susiatmi, Sandi Ari (Prosiding University Research Colloquium, 2023)
The growth and development of children in Indonesia still needs serious attention, the rate of delay in growth and development is still quite high, which is around 5?10% experiencing general developmental delays. Preparing for optimal growth and development of babies can be done since pregnancy. The purpose of this community service activity is to increase the role of husbands, families in supporting future mothers and mothers who have babies in order to ensure that the baby’s growth and development goes well and optimize the role of posyandu cadres in increasing the growth and development of babies. The targets of this activity are pregnant women, toddler mothers, husbands/families of pregnant women & mothers of toddlers in the work area of Puskesmas Bojong I. Methods are carried out by providing health counseling to husbands/families, prospective mothers and mothers of babies about the importance of preparing for optimal baby growth and development, and demonstration of practices on how to exclusively breastfeed, the first thousand days of life, early initiation of breastfeeding. The results of this activity are in the form of an increase in knowledge in pregnant women and husbands about exclusive breastfeeding results p: 0.0001 and there is an increase in the knowledge of mothers of babies and toddlers about the first thousand days of life with results p: 0.0001. Health workers, in this case midwives need to provide education to pregnant women and mothers of toddlers to optimize the growth and development of babies and toddlers.